RAJASTHAN WATER HARVESTING KNOWLEDGE TRADITION: YESTERDAY, TODAY AND TOMORROW - Thakran, Annu; Avantika (ShodhKosh: Journal of Visual and Performing Arts, 2023)
“Humans should always strive for water conservation, otherwise their thirst will never be quenched in the future”. Water occupies a primary place in our daily needs, without which life is unimaginable. Local people, in harmony with the ecosystem, developed water harvesting methods according to geographical nature, which is an excellent example of local scientific knowledge. One such example is the Indian state of Rajasthan, which has been a dry, semi-arid region, but despite being in the Thar Desert, the people here have developed a system of using every drop of water in a very systematic way. In view of the water crisis in contemporary times, today the local people are again using modern technology while reestablishing and reviving these knowledge traditions. But even in this, their knowledge and experience remains the pillar. In this research paper, we will study two contexts of the politics of knowledge, which first includes the historical journey of the Rajasthan water conservation system and second, we will also study and analyze how in contemporary times, community people have not only reworked on these systems by taking action together, but have also spread awareness through the medium of communication of art and culture for solving the problem of water conservation and water crisis in future. The state of Rajasthan is an example of how local communities have managed natural resources well through traditional knowledge and this knowledge.